The Star, 15 Oktober 2007 - Khoo, Simon (Star Publications (Malaysia) Berhad, 2007)
The ferry that caught fire while heading for Pulau Tioman on Saturday, leading to the death of four passengers, did not have a valid ship license and passenger certificate